Detection of Vascular Notch3 Deposits in Unfixed Frozen Skin Biopsy Sample in CADASIL - Ueda, Akihiko; Nakajima, Makoto; Misumi, Yohei; Nakahara, Keiichi; Shinriki, Satoru; Tasaki, Masayoshi; Matsui, Hirotaka; Ueda, Mitsuharu (Frontiers in Neurology, 2022)
This study aimed to evaluate the utility of immunohistochemical staining of vascular Notch3 deposits in biopsied unfixed frozen skin samples from patients with suspected cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). We analyzed vascular Notch3 deposits in unfixed frozen skin biopsy samples obtained from 43 patients with suspected CADASIL by immunohistochemistry using antibodies against the extracellular domain (ECD) of Notch3. We also sequenced the NOTCH3 gene in all patients, as well as evaluated their symptoms and neuroimages. We found granular Notch3 ECD deposits in the vessel walls of unfixed frozen skin biopsy samples in 10 of the 43 suspected patients with CADASIL. All 10 cases with skin Notch3 ECD deposits also carried reported pathogenic variants in the NOTCH3 gene associated with CADASIL. NOTCH3 variants of unknown significance were found in the other four patients without vascular Notch3 ECD or granular osmiophilic material deposits in biopsied skin samples. The remaining 29 cases without vascular Notch3 ECD deposits did not have variants in the NOTCH3 gene. Immunohistochemical evaluation of vascular Notch3 ECD deposits in unfixed frozen biopsied skin samples may be useful for detecting Notch3 deposits in CADASIL.